1998
DOI: 10.1021/jo981537m
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Ketone−Nitrile Reductive Coupling Reactions Promoted by Samarium(II) Iodide

Abstract: Samarium(II) iodide (SmI2) has been successfully utilized as a reducing agent for the intramolecular coupling of ketones with nitriles. The use of visible light to promote the reductive coupling represents an improvement over previously reported protocols. The procedure also avoids overreduction of the resulting α-hydroxy ketones. Monocyclic, fused bicyclic, and bridged bicyclic α-hydroxy ketones composed of a number of substitution patterns have been synthesized in moderate to excellent yield via this method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…12 The formation of an actinide ketimide complex ( 5 ) seems to be the crucial step in the synthesis of the unique 5,6‐dicyano‐1‐methyl‐3‐( N ‐methylamino)isoindolyl ligand. Numerous examples of metal‐mediated nitrile coupling reactions with compounds such as amines,13a imines,13b ketones,13c alkynes,13d amidines,13e oximes,13f and other nitriles13g are known. However, to the best of our knowledge, the coupling of a nitrile with a ketimide functional group has not been observed with transition metals, once again highlighting the differences between transition metals and the actinides.…”
Section: Methodsmentioning
confidence: 99%
“…12 The formation of an actinide ketimide complex ( 5 ) seems to be the crucial step in the synthesis of the unique 5,6‐dicyano‐1‐methyl‐3‐( N ‐methylamino)isoindolyl ligand. Numerous examples of metal‐mediated nitrile coupling reactions with compounds such as amines,13a imines,13b ketones,13c alkynes,13d amidines,13e oximes,13f and other nitriles13g are known. However, to the best of our knowledge, the coupling of a nitrile with a ketimide functional group has not been observed with transition metals, once again highlighting the differences between transition metals and the actinides.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Here, the catalyst likely initiates a ketyl radical attack to the nitrile, which leads to the formation of the methylene-bridged eight-membered ring. [12] The investigation of the first step was started using 4-quinolones and acrylonitrile as coupling partners. It was found that a mixture of titanocene dichloride (10 mol %), zinc dust, triethylamine hydrochloride, and chlorotrimethylsilane gave good results after 24 h reaction time (Table 1).…”
mentioning
confidence: 99%
“…[11a,b] This concept was now advanced towards the challenging titanium(III)-catalyzed ketonitrile cyclization forming the desired methylene-bridged tricyclic building blocks ( Table 2). [12] The polyfunctionalized tetrahydroquinolinone derivatives 1-8 were submitted to reductive umpolung conditions using 10 mol % of titanocene dichloride, zinc and slightly increased amounts of triethylamine hydrochloride and chlorotrimethylsilane. The room-temperature reaction gave the desired products 27-34 in good yields and the various functional groups that were present in the precursors were tolerated very well.…”
mentioning
confidence: 99%
“…Replacement of TBAI by other catalysts, including organocatalysts and transition-metal catalysts, did not lead to the desired product (Table 1, entries 7-10). Notably, when other common oxidants were used for this transformation, again, no significant amount of product 3 a was detected ( Table 1, entries [11][12][13]. Substituent effect on the phenyl ring of phenylacetonitrile was further investigated.…”
Section: Introductionmentioning
confidence: 99%